6. Identification of Parasites on Squid (Loligo spp.) in The Fish Auction Site (FAS) Lampulo Banda Aceh - Resty Fauzana Rahman; Muttaqien Bakrie; Muhammad Hambal; Elia Wardani; Yudha Fahrimal; Dwina Aliza; Hamdani Budiman (Universitas Syiah Kuala, 2017)
A study has been conducted on squid (Loligo spp.) in the Fish Auction Site (FAS) Lampulo Banda Aceh, in March 2016 to study and identify parasites that infect the squid as well as determine the level of the prevalence of parasites. A total 20 squid were used as samples and examined in the Laboratory of Parasitology of Veterinary Faculty Syiah Kuala University. The ectoparasite examination on the surface of the body was conducted using body scraping on mucous and skin that were observed under microscope, and the endoparasite examination conducted by observation the abdomen of squid that was placed on the petridish and observed using microscope. The study revealed that one genus of endoparasite that infected squid was Anisakis sp. with prevalence of 5%.